Transformation Pathways of China's Power Sector in the Context of "Carbon Peaking and Carbon Neutrality" - Yuan Bo; Xia Peng; Chen Haitao; Wu Cong; Sun Guangzeng (E3S Web of Conferences, 2023)
To achieve the "carbon peak" and "carbon neutrality" goals, the power industry is the main battlefield and main force. Compared with the long carbon reduction path after natural peak in major European and American countries, the carbon peak, plateau period, and transformation path under the "dual carbon" goal in China will be completely different. This article establishes a multi-scenario analysis framework for the transformation path of the power industry under the "dual carbon" goal, and constructs three major scenarios. It analyses the low-carbon transformation path of power system including power source structure and carbon emissions under different scenarios and proposes policy recommendations.